Ενεπίγραφες επιτύμβιες στήλες από το Κάστρο – Παλαιά του Βόλου - Kalaitzi, Myrina; Kravaritou, Sofia; Skafida, Evangelia (Tekmeria, 2018)
Four new inscribed funerary stelai of the Hellenistic and Roman Imperial periods are published in this article, found re-employed in the forti cation walls of the site ‘Kastro – Palaia’ in Volos. Two of them preserve relief scenes and one of them would have originally carried painted decoration, which is no longer visible to the naked eye. The inscriptions are of simple formulas and the relief scenes present no grand artistic merits, nonetheless, the mon- uments have been accorded detailed discussion, as they bear upon a number of questions, which have either not yet been discussed in a systematic way or call for further investigation: the question of the original provenance of the tombstones in connection with the question of the identi cation of the set- tlement at ‘Kastro – Palaia’ and its relations to the neighbouring Macedonian royal foundation of Demetrias and its prosopography; the Attic and atticizing tradition and trend of the funerary monuments of the area; the relief scenes of the reclining banqueters, their character and relation to the painted scenes with the same subject from Demetrias; the question of the heroization of the ‘common dead’; and, last, the re-appropriation of the theme in the Roman Im- perial period.